A Long-Term and Slow-Releasing Hydrogen Sulfide Donor Protects against Myocardial Ischemia/Reperfusion Injury - Xiaotian Sun (Nature Portfolio, 2017)
Hydrogen sulfide (H2S) has been recognized as an important gasotransmitter exerting various physiological effects, especially in the cardiovascular system. Herein we investigated the cardioprotective effects of a novel long-term and slow-releasing H2S donor, DATS-MSN, using in vivo myocardial ischemia/reperfusion (I/R) models and in vitro hypoxia/reoxygenation cardiomyocyte models. Unlike the instant-releasing pattern of sodium hydrosulphide (NaHS), the release of H2S from DATS-MSN was quite slow and continuous both in the cell culture medium and in rat plasma (elevated H2S concentrations during 24 h and 72 h reperfusion). Correspondingly, DATS-MSN demonstrated superior cardioprotective effects over NaHS in I/R models, which were associated with greater survival rates, reduced CK-MB and troponin I levels, decreased cardiomyocyte apoptosis index, increased antioxidant enzyme activities, inhibited myocardial inflammation, greater reduction in the infarct area and preserved cardiac ejection fraction. Some of these effects of DATS-MSN were also found to be superior to classic slow-releasing H2S donor, GYY4137. In in vitro experiments, cardiomyocytes injury was also found to be relived with the use of DATS-MSN compared to NaHS after the hypoxia/reoxygenation processes. The present work provides a novel long-term and slow-releasing H2S donor and an insight into how the release patterns of H2S donors affect its physiological functionality.